Morphometric and morphological analysis of the optic canal in adult human cadavers and dry skulls - Ashwini Bala Saheb Nuchhi; Sandhya Vikas Yatagiri; Veena Srinivas Harwalkar; Ravi Siddanagouda Bulagouda (Current Medicine Research and Practice, 2025)
Background: The optic canal, which connects the middle cranial fossa to the orbit, houses critical neurovascular structures. Its morphometric and morphological characteristics are essential for neurosurgical planning and anthropological studies. Aims: The objective of the study is to analyse the optic canal in adult human cadavers and compare findings with dry skulls, focusing on gender differences and anatomical variations. Materials and Methods: This osteological study included 26 cadavers and 112 dry adult human skulls. Measurements, recorded in millimetres using digital Vernier callipers, included vertical and transverse diameters, length, shape, number of canals and presence of septa. Statistical analyses included mean ± standard deviation, Independent t-tests and Chi-square tests. Results: In cadavers, the mean vertical diameter of the right optic canal (VDR) was 0.44 ± 0.11 mm (males: 0.47 ± 0.11 mm, females: 0.38 ± 0.11 mm; P = 0.038), larger than in dry skulls (0.385 ± 0.114 mm). Cadaveric canals were predominantly oval (57.7%, right), whereas dry skull canals were primarily round (78.6%, right). Unlike dry skulls, all cadaveric canals were single with no septa (6.3% double canals, 5%–6% septa). The cadaveric sample was skewed (69.2% males). Conclusion: Cadaveric optic canals exhibit larger diameters and a higher prevalence of oval shapes than dry skulls, likely due to tissue preservation. The absence of double canals and septa in cadavers simplifies surgical considerations. These findings enhance the clinical and anthropological understanding of optic canal variability.